Improving Mathematics Learning Outcomes Using Concrete Media (Real) KPK And FPB Materials In Class Vi States Of Sd Negeri 020 Tambusai, Tambusai District, Rokan Hulu Regency - Alirman Alirman (STKIP Rokania Pasir Pangaraian, 2022)
This research is to improve the learning process in terms of teacher and student activities so as to find out whether there is an increase in student mathematics learning outcomes after implementing the application of learning using concrete (real) media in class VI students of SD Negeri 020 Tambusai, Tambusai District, Rokan Hulu Regency, totaling 31 students. This research is motivated by the low learning outcomes of students and the awareness of teachers to use media that are in accordance with the subject matter. This research is a Classroom Action Research (CAR) which consists of two cycles. Data collection techniques in this study were carried out using observation techniques (field notes, observations, interviews, photos) and performance tests. The Observation Sheet will be analyzed qualitatively which aims to describe the activities of students and teachers during the learning process, while the performance test will be analyzed using the Minimum Completeness Criteria (KKM) analysis. The results showed an increase in mathematics learning outcomes for sixth grade students of SD Negeri 020 Tambusai, Tambusai District. Rokan Hulu Regency. This can be seen in student learning outcomes in the test in the first cycle and the daily test in the second cycle, where the average value of student learning outcomes in the pre-cycle is 55.81, in the first daily test the average value of student learning outcomes is 64.84 and on the second daily test the average value of student learning outcomes is 77.74. while the performance test will be analyzed with the analysis of the Minimum Completeness Criteria (KKM). The results showed an increase in mathematics learning outcomes for sixth grade students of SD Negeri 020 Tambusai, Tambusai District. Rokan Hulu Regency. This can be seen in student learning outcomes in the test in the first cycle and the daily test in the second cycle, where the average value of student learning outcomes in the pre-cycle is 55.81, in the first daily test the average value of student learning outcomes is 64.84 and on the second daily test the average value of student learning outcomes is 77.74. while the performance test will be analyzed with the analysis of the Minimum Completeness Criteria (KKM). The results showed an increase in mathematics learning outcomes for sixth grade students of SD Negeri 020 Tambusai, Tambusai District. Rokan Hulu Regency. This can be seen in student learning outcomes in the test in the first cycle and the daily test in the second cycle, where the average value of student learning outcomes in the pre-cycle is 55.81, in the first daily test the average value of student learning outcomes is 64.84 and on the second daily test the average value of student learning outcomes is 77.74.